2019
DOI: 10.1038/s41598-019-53360-6
|View full text |Cite|
|
Sign up to set email alerts
|

Association of ketamine use with lower risks of post-intubation hypotension in hemodynamically-unstable patients in the emergency department

Abstract: To determine whether ketamine use for tracheal intubation, compared to other sedative use, is associated with a lower risk of post-intubation hypotension in hemodynamically-unstable patients in the emergency department (ED), we analyzed the data of a prospective, multicenter, observational study—the second Japanese Emergency Airway Network (JEAN-2) Study—from February 2012 through November 2017. The current analysis included adult non-cardiac-arrest ED patients with a pre-intubation shock index of ≥0.9. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…10 A prospective Japanese registry study showed lower rates of hypotension in haemodynamically unstable patients without preceding cardiac arrest when induced with ketamine, compared with either midazolam or propofol. 11 In hospitalised patients with ST-elevation myocardial infarction requiring intubation, midazolam use was again associated with a greater rate of hypotension when compared with ketamine. 12 However, our own service has demonstrated an acceptable cardiovascular profile following PHEA with a standardised fentanyl-midazolam-rocuronium induction.…”
Section: Original Researchmentioning
confidence: 99%
“…10 A prospective Japanese registry study showed lower rates of hypotension in haemodynamically unstable patients without preceding cardiac arrest when induced with ketamine, compared with either midazolam or propofol. 11 In hospitalised patients with ST-elevation myocardial infarction requiring intubation, midazolam use was again associated with a greater rate of hypotension when compared with ketamine. 12 However, our own service has demonstrated an acceptable cardiovascular profile following PHEA with a standardised fentanyl-midazolam-rocuronium induction.…”
Section: Original Researchmentioning
confidence: 99%
“…This may be related to the known myocardial depressant effects of ketamine, or may be due to residual confounding related to ketamine being chosen as an induction agent in sicker patients. 20 , 21 Patient harm can be minimized by anticipating and preparing to manage these adverse effects, as well as having skilled and experienced team members working as a cohesive unit. 22 This is borne out by the absence of periprocedural cardiac arrest in our population, which was associated with prompt administration of supplemental vasopressors in appropriate doses.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective observational study of patients undergoing rapid sequence intubation with ketamine in the out-of-hospital setting, hypotension was observed in up to 24% in patients with high shock index, whereas patients with low shock index had sustained increase in blood pressure and heart rate ( 22 ). In a prospective multicenter study of intubation in hemodynamically unstable patients, ketamine exposure was associated with 15% postintubation hypotension albeit less than the 25% seen with midazolam-propofol combination ( 23 ). So, the assumption that ketamine is safe to use in hemodynamically unstable patients may be misleading as some patients may experience potentially sustained paradoxical hypotension.…”
Section: Discussionmentioning
confidence: 99%